2017
DOI: 10.1007/s00431-017-2983-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in home-ventilated children and their families

Abstract: Perceived QOL by children with HMV and their families is lower than that of healthy children. Parents are happy to care for their children at home, even though it negatively affects family life. What is Known: • The use of home mechanical ventilation (HMV) in children has increased over the last years. • Normal family functioning is usually disrupted by HMV. What is New: • The aim of HMV is to provide a lifestyle similar to that of healthy children, but perceived quality of life by these patients and their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(113 citation statements)
references
References 41 publications
8
98
2
5
Order By: Relevance
“…This study found that children on HMV had lower HRQoL compared to healthy controls, in most domains. These findings are consistent with a recent Spanish study of 41 children (mean age 8.2 years) whose global scores in the PedsQL questionnaire were below those of published normative data for healthy children 8 . In a Canadian study, which also used the HUI2/3 questionnaires, HRQoL of children on HMV was lower than published literature for healthy children 27 …”
Section: Discussionsupporting
confidence: 89%
“…This study found that children on HMV had lower HRQoL compared to healthy controls, in most domains. These findings are consistent with a recent Spanish study of 41 children (mean age 8.2 years) whose global scores in the PedsQL questionnaire were below those of published normative data for healthy children 8 . In a Canadian study, which also used the HUI2/3 questionnaires, HRQoL of children on HMV was lower than published literature for healthy children 27 …”
Section: Discussionsupporting
confidence: 89%
“…The high proportion of patients on ventilator support ≥16 hours per day (ie, permanent ventilation) further underscores the morbidity of this severe neuromuscular disease. Children requiring this level of support are unlikely to have intrinsic capacity to wean and would die without such interventions21; in addition, they and their families face substantial physical, emotional and financial demands associated with their need for mechanical ventilation 11–13. One cannot discount the possibility that some patients felt likely to do better by their managing care teams might have been more likely to be offered intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Most who survive infancy require mechanical ventilation and supplementary feeding, rely on wheelchairs for mobility, undergo multiple surgeries in their first year of life and die in early childhood 9 10. Those who survive face substantial physical, emotional and financial demands related to their reliance on life-sustaining ventilatory and other forms of support 11–13…”
Section: Introductionmentioning
confidence: 99%
“…In total, 43 families of children with neuromuscular disease treated in the University medical center Hamburg-Eppendorf and the Children’s Hospital Altona were evaluated with standardized questionnaires and compared to a cohort of healthy children and children with other chronic diseases, respectively. In view of previous reports on health-related quality of life in ventilated patients [ 10 , 12 , 14 , 16 ] we propose that long-term ventilation is one factor that impairs quality of life of affected children and their families due to an increase in disease burden.…”
Section: Introductionmentioning
confidence: 84%